Particle acceleration in shearing flows: the self-generation of turbulent spine-sheath structures in relativistic magnetohydrodynamic jet simulations - Wang, Jie-Shuang; Reville, Brian; Mizuno, Yosuke; Rieger, Frank M.; Aharonian, Felix A (Monthly notices of the Royal Astronomical Society, 2023)
X-ray observations of kiloparsec-scale extragalactic jets favour a synchrotron origin. The short cooling times of the emitting electrons require a distributed acceleration of electrons up to sub-PeV energies. In a previous paper, we found that this can be self-consistently explained by a shear acceleration model, where particles are accelerated to produce power-law spectra, with the spectral index being determined mainly by the velocity profile and turbulence spectrum. In this paper, we perform 3D relativistic magnetohydrodynamic simulations to investigate the formation of a spine-sheath structure and the development of turbulence for a relativistic jet propagating into a static cocoon. We explore different spine velocities and magnetic field profiles, with values being chosen to match typical Fanaroff-Riley type I/II jets. We find that in all cases a sheath is generated on the interface of the spine and the cocoon mainly as a result of the Kelvin-Helmholtz instability. The large-scale velocity profile in the sheath is close to linear. Turbulence develops in both the spine and the sheath, with a turbulent velocity spectrum consistent with Kolmogorov scaling. The implications for shear particle acceleration are explored, with a focus on the particle spectral index.
Veröffentlicht: 30. Dezember 2022
Gesehen am 29.03.2023